The Incremental Shuttle Walk Test in Older Brazilian Adults - Juergensen, Soraia Pilon; de Oliveira Antunes, Leticia Claudia [UNESP]; Tanni, Suzana Erico [UNESP]; Banov, Marcos Carraro [UNESP]; Lucheta, Paulo Adolfo [UNESP]; Bucceroni, Alessandra Freire [UNESP]; Godoy, Irma de [UNESP]; Dourado, Victor Zuniga (Karger, 2011)
Background: Despite widespread use of the incremental shuttle walk distance (ISWD), there are no reference equations for predicting it. Objectives: We aimed to evaluate ISWD in healthy subjects and to establish a reference equation for its prediction. Methods: 131 Brazilian individuals (61 males; 59 +/- 10 years) performed 2 walk tests in a 10-m long corridor. We assessed height, weight, body mass index, forced expiratory volume in 1 s, forced vital capacity and self-reported physical activity. Results: Mean ISWD was greater in males than in females (606 +/- 167 vs. 443 +/- 117 m; p < 0.001). ISWD correlated significantly (p < 0.05) with age (r = -0.51), height (r = 0.54) and weight (r = 0.20). A predictive model including age, height, weight and gender explained 50.3% of the ISWD variance. In an additional group of 20 subjects prospectively studied, the difference between measured and predicted ISWD was not statistically significant (534 +/- 84 vs. 552 +/- 87 m, respectively), representing 97 +/- 12% of the predicted value calculated with our reference equation for ISWD. Conclusions: This reference equation including demographic and anthropomorphic attributes could be useful for interpreting the walking performance of patients with chronic diseases that affect exercise capacity. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Shuttle walk; Exercise testing; Reference values